Adaptation of Drosophila melanogaster to Long Photoperiods of High-Latitude Summers Is Facilitated by the ls-Timeless Allele. Issue 2 (April 2022) - Deppisch, Peter; Prutscher, Johanna M.; Pegoraro, Mirko; Tauber, Eran; Wegener, Christian; Helfrich-Förster, Charlotte
Circadian clocks help animals to be active at the optimal time of the day whereby for most species the daily light-dark cycle is the most important zeitgeber for their circadian clock. In this respect, long arctic summer days are particularly challenging as light is present almost 24 h per day, and continuous light makes the circadian clocks of many animals arrhythmic. This is especially true for the fruit fly, Drosophila melanogaster, which possesses a very light-sensitive clock. The blue-light photoreceptor Cryptochrome (CRY) and the clock protein Timeless (TIM) are the light-sensitive components of the circadian clock and are responsible for constant light-induced arrhythmicity even at very low light intensities. Nevertheless, D. melanogaster was able to spread from its tropical origin and invade northern latitudes. Here, we tested whether a natural polymorphism at the timeless ( tim ) locus, s-tim and ls-tim, helped adaptation to very long photoperiods. The recently evolved natural allele, ls-tim, encodes a longer, less light sensitive form of TIM (L-TIM) in addition to the shorter (S-TIM) form, the only form encoded by the ancient s-tim allele. ls-tim has evolved in southeastern Italy and slowly spreads to higher latitudes. L-TIM is known to interact less efficiently with CRY as compared with S-TIM. Here, we studied the locomotor activity patterns of 40 wild s-tim and ls-tim isofemale lines caught at different latitudes under simulated high-latitude summer light conditions (continuous light or long photoperiods with 20-h daily light). We found that the ls-tim lines were significantly more rhythmic under continuous light than the s-tim lines. Importantly, the ls-tim lines can delay their evening activity under long photoperiods, a behavioral adaptation that appears to be optimal under high-latitude conditions. Our observations suggest that the functional gain associated with ls-tim may drive the northern spread of this allele by directional selection.